Technology Innovation Management in Indonesian Language Learning Based on Digital Literacy - Sinta Dewi Ginoga (Civiliza Publishing, Indonesia., 2026)
The importance of technology integration in learning has not been fully optimized due to weak managerial aspects in managing learning innovations. This study aims to analyze and develop the concept of managing technological innovation in Indonesian language learning based on digital literacy, thereby improving the quality of learning and students' literacy competencies in the digital era. This study uses a qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation studies. Data were analyzed using qualitative descriptive analysis techniques through data reduction, data presentation, and drawing conclusions. The results show that the management of technological innovation in Indonesian language learning has been implemented through four main functions: planning, organizing, implementing, and evaluating. Planning is carried out by integrating digital literacy into technology-based learning tools. Organization is supported by the availability of infrastructure, although there are still limitations in teacher competency in utilizing technology. The implementation of digital-based learning shows increased interactivity, student participation, and digital literacy skills, especially in understanding and producing texts. Digital-based evaluation through portfolios and projects also shows an increase in students' critical thinking skills. The conclusion of this study confirms that technological innovation management plays a significant role in improving the quality of Indonesian language learning based on digital literacy.